Comportamento da rebarba no fresamento de faceamento do aço inoxidável PH 13 8Mo - Silva, Luiz Carlos da (2011)
This thesis aims to investigate the formation of burrs in face milling milling of PH 13 8Mo stainless steel. Cemented carbide inserts were used in a 63 mm of diameter milling cutter. The tests were divided into two stages. In the first stage the following variables were studied: application of cutting fluid, tool geometry, loading of the cutter (cutting width), depth of cut and milling with the remaining burrs from previous cut. The depth of cut was considered for studying the transition from primary to secondary burr. In the second stage of testing the best results encountered in the first part were applied, considering the conditions that gave the lowest burr height. A central composite design was used varying the cutting speed, the feed rate, the depth of cut, the flank wear and the exit angle of the cutter from the workpiece. The burrs were measured at six different points of the workpiece border using a system of reproduction of the burr with the help of a silicon mass that after frozen reveals the negative forms of the burrs with measurements in a stereomicroscopy. It was found that the application of a cutting fluid has not affected the dimensions of the burrs, but the same did not happen with the remaining burr from previous cut. Burr was also smaller when the higher level of the feed rate and the lower levels of the depth of cut, the exit angle and the tool wear were used. Variation of cutting speed was not statistically significant for determining the burr size. The secondary burr was observed in a few numbers of tests, making this event unimportant here. The methodology applied allowed the development of a model as a function of the main input variables and optimization targeting minimum burr sizes.